Analisis Kualitas Pelayanan dan Pengaruhnya terhadap Loyalitas Pelanggan - Emila Sholiha (IPM2KPE, 2022)
This study aims to examine the influence of service quality variables (ie physical evidence, implementation, responsiveness, assurance, and empathy) on customer loyalty. This research method is descriptive quantitative. Data analysis used multiple linear regression, F-test and t-test were used to analyze the data. The results showed that the tcount of each independent variable had a significance value of 0.000, or less than (0.05). In conclusion, the variables of service quality, service, responsiveness, assurance, and empathy have a significant effect on customer loyalty at PT. Pos Indonesia (Persero) Lahat Post Office, either simultaneously or partially. Furthermore, the identified service quality reliability variables affect customer loyalty. Keywords: Physical Evidence, Responsiveness, Empathy, Assurance, Reliability, Customer Loyalty, Service Quality